Designing Knowledge Strategies for Universities in Crazy Times - BRATIANU, Contantin (Management Dynamics in the Knowledge Economy, 2020)
The purpose of this paper is to analyze the challenges universities have during crazy times and to show how to design knowledge strategies to navigate successfully through the changing economic landscape. Crazy times mean times of rapid and unpredictable changes in the economic environment, times of crises, and disruptive phenomena. For such kind of new realities, the deliberate strategies designed for a predictable future cannot help anymore. They should be replaced by emergent strategies, which consider a moving time coming from the future towards us. Universities are knowledge-intensive organizations, and knowledge is a strategic resource. Designing knowledge strategies and integrating them into the university business strategies becomes a new necessity. Our research is based on a conceptual analysis of time perception and strategy design for strengthening the university competitiveness in a changing environment. We make use of the known-unknown matrix and search for those generic strategies which contribute to the renewal of intellectual capital and achieving a competitive advantage in the new global market of higher education. The quest for becoming a world-class university and the pressure of the ranking systems require a special focus on designing and implementing knowledge strategies.